Surgical Outcomes of Posterior Spinal Fusion Alone Using Cervical Pedicle Screw Constructs for Cervical Disorders Associated With Athetoid Cerebral Palsy. Issue 24 (15th December 2017) - Watanabe, Kei; Hirano, Toru; Katsumi, Keiichi; Ohashi, Masayuki; Shoji, Hirokazu; Yamazaki, Akiyoshi; Izumi, Tomohiro; Hasegawa, Kazuhiro; Ito, Takui; Endo, Naoto
Abstract : Study Design: Retrospective case series. Objective: The aim of this study was to investigate clinical outcomes after posterior spinal fusion (PSF) using cervical pedicle screw (CPS) constructs for cervical disorders associated with athetoid cerebral palsy (CP). Summary of Background Data: Traditionally, most patients with cervical myelopathy associated with CP have required combined anterior and posterior fusion to achieve solid stability against severe involuntary movement. Methods: Thirty-one CP patients with cervical disorders who underwent PSF alone with a minimum 2-year follow-up (mean 58 months) were analyzed. All patients were treated with PSF using CPS constructs with or without decompression procedures. The average number of fused segments was 5.1 (range, 1–10 segments), and a halo jacket was applied in 16 patients for at least 2 months after surgery. Clinical outcomes using the Japanese Orthoedic Association scoring system (JOA score) and walking ability, radiographic sagittal alignment, fusion status, and surgery-related complications were evaluated. Results: The JOA score improved from 8.3 points preoperatively to 10.9 points at the final follow-up ( P  < 0.05). Although no patients experienced deterioration in their walking ability postoperatively, 10 patients were unable to walk at the final follow-up. Sagittal alignment, including C0-2 angle, C2-7 angle, and local alignment in fused segments, was maintained postoperatively. Twenty-five patients achieved fusion at the final follow-up (fusion rate: 81%), and fivepatients with nonunion required additional surgery. With regard to complications, 5 patients encountered postoperative upper extremity palsy. Conclusion: The CPS construct is amenable to achieve a relatively high fusion rate without correction loss, and good clinical outcomes can be achieved with a posterior single approach for CP patients. In the future, efforts should be made to make appropriate decisions regarding the fusion area, take preventative measures against postoperative upper extremity palsy, and simplify external orthoses after surgery, especially with the use of a halo jacket. Level of Evidence: 4